Comprehensive Atlas of Circulating Rare Cells Detected by SE-iFISH and Image Scanning Platform in Patients With Various Diseases - Hu, Binjie; Gong, Yanping; Wang, Yulan; Xie, Jianzhu; Cheng, Jin; Huang, Qian (Frontiers in Oncology, 2022)
Objective: Circulating rare cell (CRC) is known as a crucial nucleated cellular response to pathological conditions, yet the landscape of cell types across a wide variety of diseases lacks comprehensive understanding. This study aimed to detect and present a full spectrum of highly heterogeneous CRCs in clinical practice and further explored the characterization of CRC subtypes in distinct biomarker combinations and aneuploid chromosomes among various disease groups. Methods: Peripheral blood was obtained from 2360 patients with different cancers and non-neoplastic diseases. CRCs capture and identification were accomplished using a novel platform integrating subtraction enrichment and immunostaining-fluorescence in situ hybridization (SE-iFISH) strategy with a high-throughput automated image scanning system, on which hemocyte, tumor, epithelial, endothelial, mesenchymal and stemness biomarkers were immunostained and displayed simultaneously. Double chromosome enumeration probes (CEP8 & CEP12) co-detection was performed on isolated CRCs from an extended trial for two chromosome ploidy patterns. Results: A comprehensive atlas categorizing the diverse CRCs into 71 subtypes outlining was mapped out. The presence of epithelial-mesenchymal transition (EMT) or endothelial-mesenchymal transition (EndoMT), the cells with progenitor property, hematologic CRCs expressing multiple biomarkers, CRCs at “naked nuclei” status and the rarely-reported aneuploid mesenchymal epithelial-endothelial fusion cluster were described. Circulating tumor cells (CTCs) were detected in 2157 (91.4%) patients, the total numbers of CTCs and circulating tumor-derived endothelial cells (CTECs) were relatively higher in several digestive system cancer types and non-neoplastic infectious diseases (P<0.05). Co-detection combining CEP8 and CEP12 showed a higher diagnostic specificity on account of 57.27% false-negative of CRC detection through a single probe of CEP8. Conclusions: The alternative biomarkers and chromosomes to be targeted by SE-iFISH and the image scanning platform, along with the comprehensive atlas offer insight into the heterogeneity of CRCs and reveal potential contributions to specific disease diagnosis and therapeutic target cells discovery.